Optimizing maize systems with raised beds: boosting productivity, profitability, and sustainability - Jat, Raj Kumar; Meena, Vijay Singh; Reddy, Illathur R.; Sohane, R. K.; Singh, R. N.; Durgude, Shubham; Kumar, Suneel; Pazhanismy, S.; Meena, Sunita Kumari; Sharda, Kumari; Singh, Susheel; Singh, Rama Kant; et al. (Frontiers in Sustainable Food Systems, 2025)
Maize is an economically important cereal crop, whose adaptability to a variety of agroecological zones and uses as a food, feed, and input in various industries has ensured its global importance. In this study, the implications of the raised bed planting (RBP) system on smallholder maize farming in Bihar, India, for four consecutive Rabi seasons were evaluated from 2020–2021 to 2023–2024. The research focuses on key parameters such as productivity, profitability, water use efficiency (WUE), and nutrient use efficiency (NUE) to present a sustainable alternative to traditional flatbed planting systems. Maize yield at RBP ranged from 9.28 to 10.53 t ha−1, significantly higher than the range of 5.70 to 8.29 t ha−1 for flatbed (FB). The raised bed planting (RBP) system was more profitable as well, where net return increased by 20% compared to the FB system. WUE was 35% better in the RBP system, and NUE (grain yield per unit of applied N) was 25% better than FB systems. RBP enhances water and nutrient (nitrogen, phosphorus, and potassium) use efficiency, boosting productivity and profitability.